2019
DOI: 10.24036/jmpe.v1i3.4989
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Faktor-Faktor Yang Mempengaruhi Utang Luar Negeri Di Indonesia

Abstract: This study aims to determine and analyze the factors that influence foreign debt in Indonesia with variables that effect economic growth, inflation, and foreign interest rates. This type of research is associative descriptive research, where the data used is secondary data from 1970 to 2017 obtained from institutions and related institutions, which are analyzed using the Error Correction Model (ECM) method. This study initially used the Ordinary Lest Square (OLS) method to see long-term, and used ECM because i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0
14

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 0 publications
3
5
0
14
Order By: Relevance
“…The results of this study are in line with Rizqiansyah (2019), Ginting (2016), Trisdian (2015), and Saputra and Nugroho (2014) who found that the money supply has a significant positive effect on inflation. Likewise, Maggi and Saraswati (2013) found that the money supply had a significant positive effect in the long run on inflation in Indonesia.…”
Section: Estimation Test Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The results of this study are in line with Rizqiansyah (2019), Ginting (2016), Trisdian (2015), and Saputra and Nugroho (2014) who found that the money supply has a significant positive effect on inflation. Likewise, Maggi and Saraswati (2013) found that the money supply had a significant positive effect in the long run on inflation in Indonesia.…”
Section: Estimation Test Resultssupporting
confidence: 90%
“…Likewise with Saputra and Nugroho (2014) who in their research found that individually, the money supply and the exchange rate had a significant positive effect, while interest rates had a positive but insignificant effect on inflation in Indonesia.…”
Section: Estimation Test Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…Higher levels of inflation can disrupt economic growth in a region, and conversely inflation that is too low can also cause sluggishness in the economy that occurs in a particular region (Septiatin et al, 2016). Therefore, stable inflation needs to be maintained, so that economic growth becomes strong (Saputra & Nugroho, 2014). The economic growth of a country, including Indonesia, will not be free from inflation.…”
Section: Resultsmentioning
confidence: 99%
“…Those joint variables can explain 56,1% of the changes that happen in inflation as showed in the Rsquared value, while the other 43,9% is influenced by other variables that are not included in the estimation model. In other hands, Saputra and SBM (2014) who operated an ARCH/GARCH model, revealed that the changes of inflation can be explained by variables such as the money supply, exchange rates, interest rate, and rice prices as the representative of volatile foods. Whereas, the money supply, exchange rates, and rice prices are positive and significantly influence inflation, while the interest rate even tough positive it does not significantly influence inflation.…”
Section: Introductionmentioning
confidence: 99%